Review on the mechanical properties of rubberized geopolymer concrete - Azunna, Sunday U.; Abd Aziz, Farah Nora Aznieta; Abbas Al-Ghazali, Noor; Rashid, Raizal S.M.; A. Bakar, Nabilah (Elsevier, 2024)
Rubberized geopolymer concrete (RuGPC) is a new, environmentally safe building material requiring less energy and carbon footmark than normal cement-based systems, which can significantly reduce global warming concerns. Using waste rubber tyres by incorporating them in concrete as a substitute for natural aggregate, helps to reduce pollution and depletion of natural resources. Research shows that incorporating waste crumb rubber in geopolymer concrete (GPC) can reduce carbon dioxide emissions by 90% compared to ordinary Portland cement (OPC) and attain sufficient and mechanical properties and durability. This paper reviews the material properties of RuGPC and the possible structural application. It can be concluded, that RuGPC can substitute normal concrete (NC) particularly due to its impact resistance, and energy absorption performance. However, more research still needs to be conducted to be able to come up with practical design standards and conduct full-scale studies on RuGPC elements structurally to promote its practicability.